The Impact of the Failure-based Learning Behavior on Organizational Agility from the Workers’ Point of View in the Jordanian Industrial Companies in King Abdullah II Industrial City - Sahab - AL-Faouri, Elham Hmoud; Al-Rfou, Ahmad Nahar (International Review of Management and Marketing, 2017)
This study aims to investigate the impact of failure-based learning behavior on organizational agility dimensions including customer agility, operation agility, as well as supply and distribution agility from the respondents’ point of view in 358 Jordanian industrial companies at King Abdullah II Industrial City in Sahab. A random sample of 80 companies was chosen, and the sampling unit covered individuals working at the companies. The studied community consisted of (700) administrators according to the statistics and records of these companies. And (350) questionnaires were distributed. The researcher retrieved (290) questionnaires, which are accounted for (83%) of the questionnaires distributed and excluded (35) questionnaire since it was not filled completely. Thus, the sample of this study consisted of (255) units. Data was analyzed using the statistical package for the social sciences (SPSS 20), descriptive statistics measurement and simple regression. The results showed a statistically significant effect of the failure-based learning behavior on organizational agility including its different dimension. In light of the results obtained, the study suggests the institutionalize failure-based learning behavior, in order to use in organizational learning and support the agility. Keywords: Organizational Agility, Failure-Based Learning Behavior, Organizational Learning, Industrial Companies JEL classifications: D23, L15, L2